Under the surface: a survey of principles of language use in advanced L2 speakers - Lambert, Monique; Stutterheim, Christiane von; Carroll, Mary; Gerwien, Johannes (Language, interaction and acquisition, 2022)
Abstract Through a survey of crosslinguistic empirical studies on narratives and in the domain of motion events, we argue that the principles of language use pose a hurdle for second language acquisition, an issue that has not been given adequate attention in earlier research. These principles are part of our pragmatic knowledge which encompasses language-specific information organization at the discourse level as well as event schemata at the level of construing reportable units. The findings show how highly competent L2 speakers activate L1-based knowledge that reflects deeply entrenched principles and seems resistant to change.